Equivalence of Möbius Transformation and Lorentz Transformation - Kumar, Nand Kishor; Yadav, Dipendra Prasad (The Mega Journal, 2024)
The equivalence between the Möbius group acting on and the proper orthochronous Lorentz group on world vectors is reviewed. This relationship will be used to characterize how celestial spheres change with Lorentz transformations.